{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

solution_set1

solution_set1 - EE 511 Solutions to Problem Set 1 1(i A A =...

This preview shows pages 1–2. Sign up to view the full content.

EE 511 Solutions to Problem Set 1 1. (i) A + A = S and A A = φ . Therefore, P ( A ) + P ( A ) = P ( S ) = 1 and P ( A ) = 1 - P ( A ). (ii) P ( A ) 0. Therefore, P ( A ) 1. (iii) φ + S = S and φS = φ . Therefore, P ( φ ) + P ( S ) = P ( S ) and P ( φ ) = 0. (iv) B = BS = B ( A 1 + ... + A n ). Since BA i and BA j are disjoint for i 6 = j , P ( B ) = P ( BA 1 ) + P ( BA 2 ) + ... + P ( BA n ). 2. B = A + AB where A ( AB ) = φ . Therefore, P ( A ) + P ( AB ) = P ( B ). Since P ( AB ) 0, P ( A ) P ( B ). 3. A + B = A + AB with A ( AB ) = φ . Therefore, P ( A + B ) = P ( A ) + P ( AB ). Similarly, B = ( A + A ) B = AB + AB . Therefore, P ( B ) = P ( AB ) + P ( AB ). Substituting this in the equation for P ( A + B ), we get P ( A + B ) = P ( A ) + P ( B ) - P ( AB ) Now, P(A+B+C) = P((A+B)+C) = P(A+B) + P(C) - P((A+B)C) = P(A) + P(B) - P(AB) + P(C) - P(AC + BC) = P(A) + P(B) + P(C) - P(AB) - (P(AC) + P(BC) - P(ACBC)) = P(A) + P(B) + P(C) - P(AB) - P(AC) - P(BC) + P(ABC) 4. We want to show P ( N X i =1 A i ) N X i =1 P ( A i ). This can be done in several ways. Solution 1: We have shown in problem 3 that P ( A + B ) = P ( A ) + P ( B ) - P ( AB ), i.e., P ( A + B ) P ( A ) + P ( B ). Using this result repeatedly, we get P ( N X i =1 A i ) = P ( A 1 + N X i =2 A i ) P ( A 1 ) + P ( N X i =2 A i ) P ( N X i =2 A i ) = P ( A 2 + N X i =3 A i ) P ( A 2 ) + P ( N X i =3 A i ) .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}